Intercellular adhesive selectivity. III. Species selectivity of embryonic liver intercellular adhesion (The Rockefeller University Press, 1976)
A species difference in the intercellular adhesive selectivity of mixtures of embryonic liver cells is reported. This is first quantitative assessment of species differences in the intercellular adhesive properties of embryonic cells. A collecting aggregate assay, a new double-label assay procedure, and histological and autoradiographic procedures were used to elucidate the intercellular adhesive selectivity of developing mammalian and avian liver cells. Evidence is presented that the reported adhesive differences are not due to the different cell types composing the respective embryonic mammalian and avian livers. Finally, such heterolgous-homotypic selectivity of adhesion is not a property of all tissues, since it is shown that developing brain cells (mesencephalon) do not exhibit the avove intercellular adhesive selectivity (mammalian vs. avian). These findings provide further support for the hypothesis that generic identity as well as cell type may play an important part in determining the intercellular adhesive behavior of heterologous-homotypic mixtures of embryonic cells. A possible evolutionary divergence of morphogenetic mechanisms is discussed.